(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2016)
In the past decade, the discourse around digital cinema has flourished and given birth to a long series of ontological and phenomenological reflections around the status of the medium in the digital age. Can digital cinema still be called ‘cinema?’. Does cinema conserve its indexical nature, or is digital cinema just a simulation? What are the effects of the proliferation of screens, and the consequent loss of the centrality of movie theaters as the place for consumption of moving images? With my essay, I would like to investigate the status of digital preservation within the world of digital cinema. How is digital preservation different from analog preservation, if at all? And how are digitally restored moving images different from a film shot digitally? If a digital image is a simulation of reality, rather than a trace left by it (as the analog image supposedly was), what is the status of the digitization of an analog photographic image? I will argue that digital preservation forces us to reconsider the analog-digital opposition, and provides a framework through which to rethink not only the present state of cinema, but also its past and the future of its history.